2018
DOI: 10.1038/s41598-018-29602-4
|View full text |Cite|
|
Sign up to set email alerts
|

Downstream Products are Potent Inhibitors of the Heparan Sulfate 2-O-Sulfotransferase

Abstract: Heparan Sulfate (HS) is a cell signaling molecule linked to pathological processes ranging from cancer to viral entry, yet fundamental aspects of its biosynthesis remain incompletely understood. Here, the binding preferences of the uronyl 2-O-sulfotransferase (HS2ST) are examined with variably-sulfated hexasaccharides. Surprisingly, heavily sulfated oligosaccharides formed by later-acting sulfotransferases bind more tightly to HS2ST than those corresponding to its natural substrate or product. Inhibition assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 73 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…These data are in line with the described stepwise mechanism underlying HS biosynthesis, further supporting that epimerization and 2- O -sulfation reactions usually take place prior to 6- O -sulfation ( Figure 1 ). More recently, it was uncovered that 6- O -sulfated HS oligosaccharides were able to bind to 2OST1, with higher affinity than 2OST1 direct substrates, and inhibit its catalytic activity ( 42 ). In light of these results, it was hypothesized that enzymes involved in the HS biosynthetic pathway might be temporarily and/or spatially separated from the intermediate substrates produced downstream on the Golgi.…”
Section: Hs Biosynthesis and Modificationmentioning
confidence: 99%
“…These data are in line with the described stepwise mechanism underlying HS biosynthesis, further supporting that epimerization and 2- O -sulfation reactions usually take place prior to 6- O -sulfation ( Figure 1 ). More recently, it was uncovered that 6- O -sulfated HS oligosaccharides were able to bind to 2OST1, with higher affinity than 2OST1 direct substrates, and inhibit its catalytic activity ( 42 ). In light of these results, it was hypothesized that enzymes involved in the HS biosynthetic pathway might be temporarily and/or spatially separated from the intermediate substrates produced downstream on the Golgi.…”
Section: Hs Biosynthesis and Modificationmentioning
confidence: 99%
“…As noted above, knowledge of the effective concentration of immobilized DNA was critical to data interpretation. For ForteBio High Precision Streptavidin (SAX) tips, we determined this value was most frequently~2 × 10 −9 M. Thus, for a reaction to be in the equilibrium binding regime, its K d value must be >10 −8 M. The binding affinities measured by Theiker et al 19 for a sulfotransferase binding to hexasaccharides ranged from 10 −8 to 10 −7 M. These experiments used slightly different Forte-Bio streptavidin tips than the current work (SA rather than SAX), but if the tips have comparable numbers of binding sites, these reactions should have been in the equilibrium binding regime. In addition, we obtained a reasonable estimate of K d for an experiment in the intermediate binding regime using Equation (2) for global fitting of multiple replicates.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Thieker et al used BLI amplitudes to monitor carbohydrate-protein titrations and thereby determine binding affinities. 19 However, they did not have a well-established technique available by which to benchmark their measurements. In particular, one must establish whether the concentration of the immobilized substrate is above or below the K d of the binding reaction, because the two scenarios require different data fitting and interpretation.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…A substrate specificity analysis showed that the 2-OST acceptor residues must be flanked by two GlcNS, consistently with the observation that N- sulfo groups mediated many contacts with several amino acids of the enzyme [ 187 ]. Oligosaccharides containing a 6- O -sulfate group also bound strongly to the 2-OST active site, but the 6- O -sulfate moiety appeared to occupy the PAPS binding site and thus inhibited the 2- O sulfation reaction [ 188 ]. Altogether, these data suggest 2- O -sulfation occurs prior to 6- O -sulfation to generate IdoA2S-GlcNS6S sequences and that the 2-OST exhibits multiple structural features to recognize its substrate sulfation pattern.…”
Section: Heparan Sulfate Maturationmentioning
confidence: 99%